Interleukin‐4‐induced loss of CD8 expression and cytolytic function in effector CD8 T cells persists long term in vivo. Issue 2 (23rd April 2013) - Olver, Stuart; Apte, Simon H.; Baz, Adriana; Kelso, Anne; Kienzle, Norbert
Summary Activation of naive CD8+ T cells in the presence of interleukin‐4 modulates their CD8 co‐receptor expression and functional differentiation, resulting in the generation of CD8low cells that produce type 2 cytokines and display poor cytolytic and anti‐tumour activity. Although this CD8low phenotype becomes stable after about a week and can persist with further stimulation in vitro, it is not known whether it can be maintained long term in vivo. Here we report that CD8low cells derived from oval‐bumin257–264‐specific T‐cell receptor‐transgenic CD8+ T cells activated in the presence of interleukin‐4 could be detected in the spleen for at least 4 months after adoptive transfer into normal mice. A significant proportion of the long‐term surviving cells retained their CD8low phenotype in vivo and after clonal re‐activation in vitro. Although long‐term surviving CD8low cells lacked detectable cytolytic activity or perforin expression, they showed some anti‐tumour function in vivo. The persistence of functional cells with a CD8low phenotype in vivo raises the possibility that such cells can contribute to effector or regulatory responses to tumours or pathogens.